English through computers 1. - Jordan, Geoff (McGraw-Hill, 1990)
History of computers -- How a computers works -- Programming languages -- Uses of the microcomputer -- Word-procesors, data bases, and spreadsheets -- Mainframes and minis -- Computers and communication systems -- Chips are everywhere -- The future